Frequent brain metastases during treatment with BRAF/MEK inhibitors: A retrospective single institutional study. Issue 10 (29th June 2020) - Nakamura, Yoshiyuki; Ishitsuka, Yosuke; Tanaka, Ryota; Okiyama, Naoko; Watanabe, Rei; Saito, Akimasa; Furuta, Junichi; Fujisawa, Yasuhiro
Abstract: Recent clinical trials revealed that both immune checkpoint inhibitors (ICI) and BRAF/MEK inhibitors significantly prolonged survival in melanoma patients when used for both advanced stage disease and postoperative adjuvant therapy. Although BRAF/MEK inhibitors are associated with a higher objective response rate than ICI, most patients relapse during treatment. However, progression patterns during treatment with BRAF/MEK inhibitors have not been extensively investigated. Here, we retrospectively collected the data of melanoma patients initially treated with BRAF/MEK inhibitors or anti‐programmed death 1 (PD‐1) antibody monotherapy at the University of Tsukuba Hospital and compared their results. The χ 2 ‐test revealed that frequency of brain metastasis (BM) development was significantly higher in cases treated with BRAF/MEK inhibitors compared with those with anti‐PD‐1 antibody monotherapy. In addition, BM‐free survival in cases treated with BRAF/MEK inhibitors was significantly shorter than those treated with anti‐PD‐1 antibody monotherapy. Our results indicate that BM development during treatment with BRAF/MEK inhibitors may be more frequent than anti‐PD‐1 antibody monotherapy, even though the extracranial metastases are well controlled. Therefore, we recommend frequent brain examinations during treatment with BRAF/MEK inhibitors to detect BM at an early stage and to promptly administrate ICI with local radiation therapy.